Numerical analysis on broken home and its causes - Nkuturum* , C.; Paago†, C.K. (International Journal of Mathematical Analysis and Modelling, 2023)
Non-linear IHBH mathematical model with XYZ sub-compartment was used to study the dynamics of broken home and marriage repair. The existence and stability of the broken home free and endemic equilibria were discussed. The broken home free equilibrium was locally asymptotically stable with R0 < 1 and unstable with R0 > 1. Numerical simulations were conducted to confirm the analytic results. The findings were that, reducing the contact rate between the intact marriage and broken home, increases the number of marriage that go into separation and educating separators to refrain from divorce can be useful in combating the broken home. The study also shows that from the broken home free equilibrium when all parameters are fixed and 50% variation of beta and k, the intact marriage increases monotonically while separated and divorce are monotonically decreased. Again, from the Endemic equilibrium when all parameters are fixed and 50% variation of beta and k, the intact marriage fluctuates at the initial stage and later increases, the separated and divorce monotonically decreased. In further studies there should be a development of various related topics that will help in analyzing other aspects that are closely related to broken home in order to get further understanding and avoid the problem of broken home that happen to us and to give us information about the effects of broken home.